Islamophobia in France: the construction of the "Muslim problem" - Hajjat, Abdellali (Sociology of race and ethnicity, 2023)
"In 2004 France banned Muslim women from wearing veils in school. In 2010 France passed legislation that banned the wearing of clothing in public that covered the face, mainly to target women who wore burqas. President Emmanuel Macron has stated that the hijab is not in accordance with French ideals. Islamophobia in France takes many forms, both explicit and implicit, and often appears to be sanctioned by the governing bodies themselves. These cultural biases reveal how the Muslim population acts as a scapegoat for the problematic status of immigrants in France more generally. Islamophobia in France is an English translation of Abdellali Hajjat and Marwan Mohammed's Islamophobie: Comment les elites franc'aises fabriquent le "probleme musulman." In this groundbreaking book, Hajjat and Mohammed argue that Islamophobia in France is not the result of individual prejudice or supposed Muslim cultural or racial deficiencies but rather arose out of structures of power and control already in place in France. Hajjat and Mohammed analyze how French elites deploy Islamophobia as a state technology for contesting and controlling the presence of specific groups of postcolonial immigrants and their descendants in contemporary France. With a new introduction for U.S. readers, the authors unpack the data on Islamophobia in France and offer a portrait of how it functions in contemporary society"--